KESETARAAN GENDER DITINJAU DARI AKSES PENDIDIKAN DAN PEKERJAAN BAGI PEREMPUAN DI DUSUN SADE DESA REMBITAN - Widya Regina Larasati; Hamidsyukrie ZM; Sukardi (Jurusan P. IPS, FKIP, Universitas Mataram, 2022)
This study aims to determine; (1) gender equality in access to education for women in Sade Hamlet, Rembitan Village, Central Lombok Regency (2) gender equality in access to work for women in Sade Hamlet, Rembitan Village, Central Lombok Regency. This research was conducted in Sade Hamlet, Rembitan Village, Central Lombok Regency. This study used a qualitative approach with the case study method. Data collection techniques in this study used interviews, observation, and documentation. Then the data were analyzed through the stages of data reduction, data presentation, and conclusions. The results of this study found that: 1) gender equality in access to education there is gender equality between men and women where women get the same rights and opportunities in education that are equal to men, 2) gender equality in access to work for women there is equality gender relations between men and women where women get the same rights and opportunities in jobs that are equal to men.